2017
DOI: 10.1093/jxb/erx188
|View full text |Cite
|
Sign up to set email alerts
|

Measuring CO2 and HCO3− permeabilities of isolated chloroplasts using a MIMS-18O approach

Abstract: New approach to determine the inorganic carbon permeability across the chloroplast envelope, and to measure the role of aquaporin Pip1,2 on CO2 permeability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…If the changes in g m with respect to C i were attributed solely to the large permeability of the chloroplast envelope to HCO 3 − , the increase of g m with the decrease in C i would be expected. Moreover, a recent study showed the permeability of HCO 3 − to be 1.0 × 10 −8 m s −1 in A. thaliana (Tolleter, Chochois, Poire, Price, & Badger, ). Thus, the hypothesis based on the high permeability of the chloroplast envelope to HCO 3 − (Heber & Purczeld, ; Tholen & Zhu, ) may not be vital.…”
Section: Discussionmentioning
confidence: 99%
“…If the changes in g m with respect to C i were attributed solely to the large permeability of the chloroplast envelope to HCO 3 − , the increase of g m with the decrease in C i would be expected. Moreover, a recent study showed the permeability of HCO 3 − to be 1.0 × 10 −8 m s −1 in A. thaliana (Tolleter, Chochois, Poire, Price, & Badger, ). Thus, the hypothesis based on the high permeability of the chloroplast envelope to HCO 3 − (Heber & Purczeld, ; Tholen & Zhu, ) may not be vital.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in plants with their roots exposed to HCO 3 − , the proportion of HCO 3 − over CO 2 during radial transport of C inorg from soil to the stele and within the xylem sap up to the leaves may be considerably lower than in the soil solution surrounding the plant roots. The direct use of root-derived HCO 3 − by CA in chloroplasts to supply CO 2 for Rubisco is unlikely when taking into account the low chloroplast permeability of HCO 3 − (1 × 10 −8 m s −1 ) in comparison to CO 2 (range from 2.3 × 10 −4 to 8 × 10 −4 m s −1 ), which was recently shown by mass inlet mass spectrometry (MIMS) using 18 O labelled C inorg [ 131 ].…”
Section: Bicarbonate Transportmentioning
confidence: 99%
“…Note that in some cases like a concomitant use of 18 O-labeled O 2 , the presence of 18 O and C 16 O 2 in the ion source of the mass spectrometer can spontaneously generate C 18 O 16 O which needs to be corrected ( Cournac et al., 1993 ). In vivo , a CA isotope exchange assay measures the global contribution of all CAs present in the biological sample with an additional effect due to diffusion/transport of C i through the membranes ( Sültemeyer and Rinast, 1996 ; Tolleter et al., 2017 ). When a periplasmic CA is present, as it is the case in C. reinhardtii cells with an active CCM, its activity dominates the exchange kinetics ( Sültemeyer and Rinast, 1996 ).…”
Section: Mims Usage In Algal Researchmentioning
confidence: 99%